Effects of mammalian target of rapamycin and aryl hydrocarbon receptor‐mediating autophagy signaling on the balance of Th17/Treg cells during perinatal bisphenol A exposure in female offspring mice. Issue 7 (31st March 2022) - Gao, Liang; Luo, Dan; Wu, Dan; Sun, Qi; Liu, Yang; Wen, Deliang; Jia, Lihong
Abstract: Bisphenol A (BPA)'s immunotoxic properties have received increasing interest, which can lead to immune dysfunction and related disease development. However, the mechanism is not completely clear. A growing body of evidence suggests that autophagy has important roles in innate immunity, inflammatory response, and adaptive immunity. This study aimed to investigate the possible mechanisms of mammalian target of rapamycin (mTOR), aryl hydrocarbon receptor (AhR), and autophagy in Treg/Th17 imbalance induced by perinatal BPA exposure. Our results showed that the number of Th17 cells in the spleen of offspring female mice significantly increased, while the number of Treg cells decreased significantly, which was consistent with the expression levels of up‐regulation of RORγt protein and a down‐regulation Foxp3 protein. The levels of mTOR, p‐mTOR, P62, and AhR protein expression increased, and LC3 protein decreased in spleen. However, in the thymus, we found that RORγt and Foxp3 proteins changed most significantly in the low‐dose BPA group, and the same as p‐mTOR and P62 protein levels. We conjectured that the potential mechanism of the imbalance of Th17/Treg upon perinatal exposure to BPA was probably associated with autophagy dysfunction. Proper autophagy plays an important role in maintaining the homeostasis of the thymic and spleen immune system.